Mechanical and Crack-Sensing Capabilities of Mode-I Joints with Carbon-Nanotube-Reinforced Adhesive Films under Hydrothermal Aging Conditions - Xoan F. Sánchez-Romate; Jesús Martin; María Sánchez; Alejandro Ureña (Nanomaterials, 2020)
The fracture behavior and crack sensing of mode-I joints with carbon nanotube (CNT)-reinforced adhesive films were explored in this paper under hydrothermal aging conditions. The measured fracture energy of CNT-reinforced joints in grit blasting conditions is higher for non-aged samples than for neat adhesive joints (around 20%) due to the nanofiller toughening and crack bridging effects. However, in the case of brushed surface-treated adherents, a drastic decrease is observed with the addition of CNTs (around 70%) due to the enhanced tribological properties of the nanofillers. Hydrothermal aging has a greater effect in the CNT-reinforced samples, showing a more prevalent plasticization effect, which is confirmed by the R-curves of the specimens. The effects of surface treatment on the crack propagation properties was observed by electrical resistance monitoring, where brushed samples showed a more unstable electrical response, explained by more unstable crack propagation and reflected by sharp increases of the electrical resistance. Aged specimens showed a very uniform increase of electrical resistance due to slower crack propagation, as induced by the plasticization effect of water. Therefore, the proposed adhesive shows a high applicability for crack detection and propagation without decreasing the mechanical properties.